An intelligent transportation system for smart nations - Aye Myat Thu (Nanyang Technological University, 2020)
Traffic congestion is a very common problem nowadays due to the rapid increase in the number of vehicles around the world, and hence a smart or intelligent transportation system has an important role for any smart nation. The main aim of this project is to investigate and implement the image processing algorithms which helps to monitor the road traffic situation at a preferred location and time and perform the data analysis. Various algorithms are implemented to detect the vehicle count, vehicle types, speed of vehicles and the overall usage of the road as these are the important parameters to consider for any intelligent transportation system. All the algorithms were developed using MATLAB MathWorks and MATLAB Graphical User Interface (GUI) was used to manipulate the controls. A series of comparisons between different methods such as edge detection methods & image segmentation methods by adjusting different brightness level were carried out to verify the performance.